(untitled) (Journal of Fiber Bioengineering and Informatics, 2024)
Textile jewellery is a type of jewellery that has a structure or texture similar/identical to textile products. Although the practice of textile jewellery is evident, there is a lack of a comprehensive overview of the techniques, methods, and materials involved. The confusion on how to apply different fabrication techniques creates difficulty in making metal textile jewellery. The review, therefore, summarises, classifies, and compares the types, techniques, materials, and structures used to make metal textile jewellery. The analysis results show that it is essential to understand the effects produced by different processes. Textile jewellery structures with similar styles can be produced by very different processes, which can be easily confused. This paper clarifies the differences between the processes to help designers more quickly and accurately select the right process for making jewellery.